Basil Fawlty ja "esithatcherilaisuus" sarjassa Pitkän Jussin majatalo - Rami Mähkä (Finland, 2022)
The article analyses the popular British situation comedy Fawlty Towers (BBC, 1975, 1979) as a comedic representation of conservatism and its lead character, Basil Fawlty (played by John Cleese), as a ‘pre-Thatcherite’. The article discusses how Fawlty and the series can help us to understand the processes which led to Margaret Thatcher winning the election in 1979 and becoming prime minister. Fawlty promotes similar values to Thatcher, but with ambiguity as the series is a comedy; comedy makes interpretation of ideological issues problematic as it is an alternative meaning-making system to non-comedic forms.
The article understands conservatism and Thatcherism as discourses rather than political dogmas or programmes. Thatcherism, including its relationship with particular forms of conservatism, is ambivalent and in some cases contradictory. Basil Fawlty is a prime example of this. The article argues that Fawlty can be seen as a ‘pre-Thatcherite’. He is the main target of laughter and ridicule in the series, but because of his witty remarks and sarcasm we are also laughing with him, not only at him. Despite his old-fashioned conservatism, he also represents values, such as patriotism, which can be seen as identifiable across political and ideological lines. This is exactly what Thatcher accomplished in the late 1970s.